Development of information and communication services in the countries of the EAEU - Akhmetkerey Balkenzhe, Gul Jussupova, Raushan Dulambayeva, Assel Zhunussova, Bexultanov, (Opción, 2020)
The Eurasian Economic Union (after - EAEU) provides an opportunity for the growth of mutual trade, including e-commerce thanks to information and communication services. The subject of this article is the field of information and communication technology services in the EAEU countries. The purpose of the study is to investigate the state, problems, and prospects for the development of information and communication services in the EAEU countries in the context of a single market of services. As a result of the study, it became known that information and communication services in the EAEU countries are developing differentially.